KHILAFAH, IMARAH DAN IMAMAH DALAM KONSTELASI POLITIK ISLAM Analisis Komperatif tentang Wacana Bentuk Negara dan Sistem Pemerintahan - Lendrawati Lendrawati (Jurnal AL-AHKAM, 2021)
The polemic about the form of state and system of government emerged after the death of Rasulullah Muhammad SAW, because of the two roles by the Prophet Muhammad as both the bearer of both the treatise and the head of state in Medina. On the other hand there is no concrete message from him who will replace it after him. Term Khilafah, Imarah and Imamah become a study that is always uptodate in the realm of Islam politics. The word "khalifah" and "imam" have the same understanding, namely the highest leader in the Islamic State. If the "caliph" and "imam" are equally understanding, the system of government he leads, namely "Khilafah" and "Imamah", is equally meaningful; no different. The Emir of Amir also means the leader in the general scope. The Khilafah in the Islamic political constellation, there are two main issues: 1) the procedure of their appointment as the successor of Prophet Muhammad SAW in leading the Ummah of Islam. 2) the authority and power attributed to the successors of Prophet Muhammad From the dimensions of political science and the state, the activities of the Apostles in Medina carry out the duties of the government, in the vision of political science is to achieve the purpose of the state by exercising curbing and preventing clashes in society, seeking prosperity and prosperity of the people, enforcement of justice.